Solid‐phase extraction of small biologically active peptides on cartridges and microelution 96‐well plates from human urine. Issue 9 (16th October 2015) - Semenistaya, Ekaterina; Zvereva, Irina; Krotov, Grigory; Rodchenkov, Grigory
Abstract : Currently liquid chromatography – mass spectrometry (LC‐MS) analysis after solid‐phase extraction (SPE) on weak cation‐exchange cartridges is a method of choice for anti‐doping analysis of small bioactive peptides such as growth hormone releasing peptides (GHRPs), desmoporessin, LHRH, and TB‐500 short fragment. Dilution of urine samples with phosphate buffer for pH adjustment and SPE on weak cation exchange microelution plates was tested as a means to increase throughput of this analysis. Dilution using 200 mM phosphate buffer provides good buffering capacity without affecting the peptides recoveries. SPE on microelution plates was performed on Waters Positive Pressure‐96 Processor with subsequent evaporation of eluates in nitrogen flow. Though the use of smaller sample volume decreases the pre‐concentration factor and increases the limits of detection of 5 out of 17 detected peptides, the recovery, linearity, and reproducibility of the microelution extraction were comparable with cartridge SPE. The effectiveness of protocols was confirmed by analysis of urine samples containing ipamorelin, and GHRP‐6 and its metabolites. SPE after urine sample dilution with buffer can be used for faster sample preparation. The use of microelution plates decreases consumption of solvents and allows processing of up to 96 samples simultaneously. Cartridge SPE with manual рН adjustment remains the best option for confirmation. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Liquid chromatography ‐ mass spectrometry analysis after solid phase extraction was implemented for detection of GHRPs, desmoporessin, LHRH and TB‐500 short fragment in urine. Dilution of urine samples with phosphate buffer for pH adjustment and extraction on microelution plates were tested as a means to increase throughput of this analysis. This effectiveness of protocols had been confirmed by analysis of urine samples contined ipamorelin, and GHRP‐6 and its metabolites.